Correlation between Serum IL-35 Levels and Bone Loss in Postmenopausal Women with Rheumatoid Arthritis - Yuxuan Li; Lutian Yao; Siyan Liu; JishengWu; Liping Xia; Hui Shen; Jing Lu (Mediators of Inflammation)
Objective. IL-35 was reported as a crucial anti-inflammatory cytokine and could efficiently regulate bone metabolism in murine collagen-induced arthritis model. However, the relationship between IL-35 and bone health in human rheumatoid arthritis (RA) has not been clarified. In this study, the aim was to explore the correlations between IL-35 and bone loss in postmenopausal women with RA. Methods. The study included 76 postmenopausal women with RA and 53 healthy postmenopausal women as healthy controls (HCs). Serum IL-35 levels were detected by enzyme-linked immunosorbent assay. Bone mineral density (BMD) at lumbar spine 1-4 and at total hip was measured using dual-energy X-ray absorptiometry. Alkaline phosphatase (ALP), β-isomerised carboxy-terminal cross-linking telopeptide of type I collagen (β-CTX), and 25-(OH) VitD3 were measured by turbidimetric inhibition immunoassay. Results. Serum IL-35 levels were increased compared with HCs, and it positively correlated with BMD and 25-(OH) VitD3 and negatively correlated with β-CTX in postmenopausal women with RA. Furthermore, serum IL-35 levels in the increased ALP group were higher than those in the normal ALP group. Conclusions. IL-35, an important anti-inflammatory cytokine, may participate in the pathogenesis of bone loss in postmenopausal women with RA.